(untitled) (Fiep Bulletin - online, 2014)
The theoretical presuppositions of the Therapy were used Rational-Emotive-Behavior Therapy (REBT - acronym in English) developed in 1955 by Albert Ellis and presented in a conference uttered in the Congress of American Psychological Association - APA (GRIEGER, 1985). It Bases on the method of treatment of the emotional disturbances (call of ABC) and it follows the educational model of cognitive learning. It tries to turn the more durable cognitive changes through the study of the rational-emotional behavior in the following way: (the) of as the people they develop and they can overcome your own disturbances; (b) of detecting of irrational faiths; (c) of discussing, discriminating and disputing irrational faiths; (d) of changing with new effects or theories. The therapeutic model of REBT is active, directing and, largely, educational (ELLIS & DRYDEN, 1987; DiGIUSEPPE & WESSLER, 1980). they were applied the Inventories of Irrational Faiths, adapted by Charles Newmark, Ruth Ann Frerking, Louise Cook and Linda Newmark (1973) and other, of Irrational Faiths, adapted by Albert Ellis and Hayslip (1994) - both translated by Dominguez (1996) and confirmed by Siqueira (2000); they were also used the Form of Solemnity-help of the Therapy Rational-emotional-Comportamental, elaborated by Sichel and Ellis (1984), and the Scale of Faiths (JOHN M. MALOUFF & NICOLA S. SCHUTTE, 1986). We Verified as the irrational faiths in relation to the unconditional solemnity-acceptance (AAI) they influence the sport practice, limiting the expanding its, in agreement with the model of Ellis. The analysis of these information will offer subsidies for the formulation of public politics gone back to the youths’ socialization, through sport practices and of competent leisure. We analyzed the adolescents participants’ of the Project Champion University of physical education University irrational faiths - FEF of the Federal University of Amazonas - UFAM in relation to the sport practice of the soccer, taking in bill aspects than the theory of Ellis denominates of unconditional solemnity-acceptance (AAI) of that group.